Paradoks Pidana Denda dan Kurungan Pengganti dalam Tindak Pidana Korupsi - Mamoh, Petrus Meirio (Pusat Riset dan Inovasi Nasional, 2025)
Corruption in Indonesia is a serious and systemic issue. One of the legal approaches used to address this problem is the imposition of criminal fines. This study aims to evaluate the effectiveness of fines imposed on corruption offenders. The research employs a normative approach with a juridical-qualitative method, based on literature studies of relevant laws and court decisions. The findings indicate that although criminal fines are regulated under Law No. 31 of 1999 in conjunction with Law No. 20 of 2001, their implementation has not been effective. Fines can still be replaced with substitute imprisonment of up to eight months under the Indonesian Penal Code (KUHP), which is often preferred by convicted individuals. In addition, there is no clear system regarding the proportional amount of fines, deadlines for payment, or enforcement mechanisms. The lack of strict regulations concerning remission also weakens the deterrent effect. This study concludes that the regulation and enforcement of criminal fines in corruption cases have not yet provided optimal deterrence and still leave many legal loopholes that need to be addressed.